The Effectiveness of the Talaqqi Method in Tahsin Al-Quràn Learning for Students - Iqbal Hidayatsah; Danusiri Danusiri; Dartim Dartim; Eman Suherman; Rijal Wakhid Rizkillah; Mamdukh Mamdukh (ZAD Al-Mufassirin, 2026)
This mixed-methods study examined the effectiveness of a talaqqī-based tahsin strategy implemented at Masjid At‑Taqwa, Universitas Muhammadiyah Semarang, in addressing students’ limited proficiency in makhraj, tajwīd, and reading fluency. Qualitative data were collected through structured observations, document analysis, and semi‑structured interviews with purposively selected participants, including students and instructors. Quantitative data were derived from mentoring examination outcomes across two academic years, involving 2,211 students in 2023–2024 and 1,889 students in 2024–2025. The intervention  integrated the principles of talaqqī (listening, imitation, repetition, and immediate correction) within a mosque‑based learning ecosystem consisting of the daily Subuhan Maos Qur’an program and weekly activities, namely —Tahsin Monday, Tilāwah Wednesday, and Kahfian Thursday. Across both cohorts, examination results showed substantial improvement in students’ recitation competence. The pass rate increased from 82.41% (1,822 of 2,211 students) in the 2023–2024 academic year to 90.26% (1,705 of 1,889 students) in 2024–2025, while the failure rate declined from 17.59% (389 of 2,211 students) to 9.74% (184 of 1,889 students).  These quantitative trends were corroborated by observational and interview data, which revealed marked improvements in the accuracy of articulation, consistency in the application of tajwīd rules, and overall reading fluency. Participants also reported enhanced motivation, greater learning discipline, and deeper spiritual engagement with the Qur’an. This study contributes to the growing body of literature on the Qur’anic pedagogy by proposing a scalable, practice‑intensive talaqqī model for higher education. By integrating large‑scale assessment data with qualitative evidence derived from a structured campus mosque program, the study offers a replicable framework for cultivating a sustainable Qur’anic learning and strengthening religious literacy among university students. The findings further demonstrate the potential of mosque-based educational ecosystems to serve as effective platforms for fostering both technical proficiency in Qur’anic recitation and the spiritual formation of learners.